Factors associated with the effectiveness and reach of NHS stop smoking services for pregnant women in England - L. R. Vaz; T. Coleman; S. J. Fahy; S. Cooper; L. Bauld; L. Szatkowski; J. Leonardi-Bee (BMC, 2017)
Abstract Background The UK National Health Service provides Stop Smoking Services for pregnant women (SSSP) but there is a lack of evidence concerning how these are best organised. This study investigates influences on services' effectiveness and also on their propensity to engage pregnant smokers with support in stopping smoking. Methods Survey data collected from 121/141 (86%) of SSSP were augmented with data from Hospital Episode Statistics and the 2011 UK National Census. 'Reach' or propensity to engage smokers with support was defined as the percentage of pregnant smokers setting a quit date with SSSP support, and 'Effectiveness' as the percentage of women who set a quit date who also reported abstinence at four weeks later. A bivariate (i.e. two outcome variable) response Markov Chain Monte Carlo model was used to identify service-level factors associated with the Reach and Effectiveness of SSSP. Results Beta coefficients represent a percentage change in Reach and Effectiveness by the covariate. Providing the majority of one-to-one contacts in a clinic rather than at home increased both Reach (%) (β: 6.97, 95% CI: 3.34, 10.60) and Effectiveness (%) (β: 7.37, 95% CI: 3.03, 11.70). Reach of SSSP was also increased when the population served was more deprived (β for increase in Reach with a one unit increase in IMD score: 0.55, 95% CI: 0.25, 0.85), had a lower proportion of people with dependent children (β: -2.52, 95% CI: -3.82, −1.22), and a lower proportion of people in managerial or professional occupations (β: -0.31, 95% CI: -0.59, −0.03). The Effectiveness of SSSP was decreased in those areas that had a greater percentage of people >16 years with no educational qualifications (β: -0.51, 95% CI: -0.95, −0.07). Conclusions To engage pregnant smokers and to encourage them to quit, it may be more efficient for SSSP support to be focussed around clinics, rather than women's homes. Reach of SSSP is inversely associated with disadvantage and efforts should be made to contact these women as they are less likely to achieve abstinence in the short and longer term.